2012
DOI: 10.1016/j.fob.2012.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Structure of l‐rhamnose isomerase in complex with l‐rhamnopyranose demonstrates the sugar‐ring opening mechanism and the role of a substrate sub‐binding site

Abstract: l-Rhamnose isomerase (l-RhI) catalyzes the reversible isomerization of l-rhamnose to l-rhamnulose. Previously determined X-ray structures of l-RhI showed a hydride-shift mechanism for the isomerization of substrates in a linear form, but the mechanism for opening of the sugar-ring is still unclear. To elucidate this mechanism, we determined X-ray structures of a mutant l-RhI in complex with l-rhamnopyranose and d-allopyranose. Results suggest that a catalytic water molecule, which acts as an acid/base catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In addition, ring opening is a common process for the first step of sugar isomerization/epimerization, as exemplified by phosphoglucose isomer-ase, galactose mutarotase, and rhamnose isomerase (13,25,26) as well as aAGE and SeYihS (11,12). The proposed mechanisms indicated that acid (A-H) and base (B:…”
Section: Structural Insights Into the Ring Opening/closurementioning
confidence: 99%
“…In addition, ring opening is a common process for the first step of sugar isomerization/epimerization, as exemplified by phosphoglucose isomer-ase, galactose mutarotase, and rhamnose isomerase (13,25,26) as well as aAGE and SeYihS (11,12). The proposed mechanisms indicated that acid (A-H) and base (B:…”
Section: Structural Insights Into the Ring Opening/closurementioning
confidence: 99%
“…In addition, E. coli possesses L-rhamnose mutarotase (RhaM, EC 5.1.3.32), which facilitates the interconversion of the ␣ and ␤ anomers of L-rhamnopyranose, enhancing the rate of rhamnose catabolism (9); the catalytic mechanism of mutarotation can be envisaged by examining the crystal structures of the enzymes from E. coli and Rhizobium leguminosarum (9,10). By analogy of a proposed catalytic mechanism of Pseudomonas stutzeri L-rhamnose isomerase, E. coli RhaA might preferentially isomerize ␤-L-rhamnopyranose to ␤-Lrhamnulofuranose (11). This assumption is supported by the crystal structure of the complex of E. coli RhaB with ␤-L-rhamnulofuranose and ADP (12) (Fig.…”
mentioning
confidence: 99%
“…Different studies suggest the prevalence of the cyclic form (pyranose, furanose) of the selected monosaccharides (hexoses, pentose, and their derivatives) in the aqueous solutions, which can be explained by the fact that the formed cyclic hemiacetals are strain-free and more stable than the open-chain structure [56][57][58][59]. Based on the previous research works on the determination of the characteristic anomeric forms of the selected monosaccharides [60][61][62][63][64][65][66][67] and the above-mentioned findings (Table 1), the following compounds are further considered as targeting foulants: β-D-glucopyranose (Glc), β-D-galactopyranose (Gal), β-D-mannopyranose (Man), α-D-glucopyranuronic acid (GlcUA), β-L-rhamnopyranose (Rha), β-L-fucopyranose (Fuc), α-L-arabinofuranose (Ara), and β-D-glucosamine (GlcN).…”
Section: The Structure and Active Centers Of The Studied Foulantsmentioning
confidence: 99%